Sistem Pintu Otomatis Menggunakan E-KTP Berbasis Internet of Things (IoT) pada Kamar Hotel - Yulisman; Naziful Iman; Eka Sabna; Hendry Fonda (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2021)
The system of opening and closing the hotel room doors is already using RFID but its use is still not optimal because the card used is very expensive and the card used can only be one card for each room, so if the card is lost, you have to re-enter the card id. Therefore, digital electronic technology systems and devices are needed to make it easier to open the door and close the hotel room so that it can facilitate the hotel security system with automatic locks. This system and device uses an E-KTP and an Internet of Thing (IoT)-based Keypad and which functions to control the device using a NodeMCU while for a card reader with an RFID engine. The research method uses a model, namely with a prototype model for making systems and automatic room door locking system tools. The results and conclusions of the manufacture of hotel room automatic door locking systems and devices using an Internet of Thing (IoT)-based E-KTP equipped with a message LCD and keypad as a door opening solution if the RFID machine does not work. The security of hotel guests who stay is more guaranteed and can also make it easier for guests and hotel staff with an automatic hotel room door lock system. The results of the user's assessment of the work of a series of systems and tools to open and lock this automatic hotel room door are very good with a value of 88.7%.